Reading Interest Via Online Book Towards Students Group Discussion and Presentation - Helmi Noviza; Cahya Pertiwi Rahni; Shelvia Indah Cahyani; Khairul Nofri (English Instruction, 2020)
This study investigates students’ reading interest via online book towards students group discussion and presentation. Regarding reading interest, in Indonesia it can still be said to have very low reading interest. UNESCO 2012 report shows that Indonesia's reading interest index is 0.001 (Yusuf, 2013). This shows that out of 1000 people only one is interested in reading, meaning that the reading interest of the Indonesian people is still low. The tendenly to obtain information instantly or through conversation appears to be stronger than information received from the text. This article use investigate by study literature is as the main way of generating arguments in this paper. From this study, it was found that there are still many students who have low reading interest in printed book and they tend to prefer reading via online book.